KERAGAMAN PARASITOID YANG BERASOSIASI DENGAN LIRIOMYZA HUIDOBRENSIS(BLANCHARD)DANLIRIOMYZASATIVAE (BLANCHARD) (DIPTERA: AGROMYZIDAE) PADA TANAMAN KACANG-KACANGAN - SRI SUNARI, A.A.A. AGUNG (Agrotrop : Journal on Agriculture Science; Vol 1 No 1 (2011), 2012)
Diversity of Parasitoid Associated to Liriomyza huidobrensis (Blanchard) and Liriomyza sativae (Blanchard) (Diptera: Agromyzidae) on Nuts Plant. The research was aimed to determined diversity of associated parasitoids withL.huidobrensis (Blanchard) andL. sativae (Blanchar) on the nuts plant in the field. The results showed that there are 8 types of parasitoids, namelyHemiptera varicornis Girault (Hymenoptera: Eulopidae).Asecodes deluchii Boucek (Hymenoptera: Eulopidae), Neochrysocaris okazaki (Kamijo) (Hymenoptera: Eulopidae), Opius spp. (Hymenoptera: Braconidae), Pnigalio sp. (Hymenoptera; Eulopidae). Clasteroceusnrsp (Hymenoptera: Eulopidae) andSphegigaster sp. (Hymenoptera: Pteromalidae). H. varicornis, A. deluchii andOpiusspp. has a different distribution spesialisation on plants hosts and altitude. H. varicornis spread evenly across the height and location of host plants. A. deluchii dominant in the lowlands and in the plains of being, andOpius spp. important in the highlands.
Keywords: parasitoid, L. huidobrensis dan L. sativae, nuts plant.